Landuse Pattern and Its Change in the Eastern Churiya Hills of Nepal Himalaya - Bhuju, Dinesh Raj; Yonjan, Pralad B.; Baidya, Bidur M. (Ecoprint: An International Journal of Ecology, 2016)
Available with full text. Key words: Churiya range; Climate; forest Degardation; GIS; Himalaya; Soil type Ecoprint An International Journal of Ecology Vol. 14, 2007 Page: 65-71 Uploaded date: 31 May, 2011